2001
DOI: 10.1177/14703203010020010501
|View full text |Cite
|
Sign up to set email alerts
|

Role of basic amino acids of the human angiotensin type 1 receptor in the binding of the non-peptide antagonist candesartan

Abstract: To explain the insurmountable/long-lasting binding of biphenyltetrazole-containing AT 1 with the proposed model, it cannot be excluded that both amino acid residues are important for the structural integrity of the AT 1 -receptor with respect to its ligand binding properties. IntroductionThe therapeutic use of selective, non-peptide antagonists for the angiotensin II type 1 (AT 1 )-receptor in the treatment of hypertension is well established.1 Experiments with Chinese Hamster Ovary cells, which have been per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…formation of IR). This supports our current opinion that the biphenyltetrazole moiety of these molecules plays an essential role in this initial binding process [23]. For insurmountable antagonism, IR must be further converted into the tight binding (IR Ã ) state.…”
Section: Action Of Mechanism Of Insurmountable Btsartanssupporting
confidence: 79%
See 1 more Smart Citation
“…formation of IR). This supports our current opinion that the biphenyltetrazole moiety of these molecules plays an essential role in this initial binding process [23]. For insurmountable antagonism, IR must be further converted into the tight binding (IR Ã ) state.…”
Section: Action Of Mechanism Of Insurmountable Btsartanssupporting
confidence: 79%
“…Site-directed receptor mutagenesis studies involving the substitution of basic amino acids of the AT 1 -receptor into neutral amino acids has already revealed that Lys 199 is involved in the binding of the carboxyl terminus of Ang II [30,31]. Likewise, mutation studies also plead for an important role of Lys 199 in the formation of IR Ã [23,32]. This fits nicely with the initial concept for the elaboration of BTsartans: that is, that their carboxyl group should interact with the same positive amino acid residue of the receptor as the carboxyl terminus of Ang II [33].…”
Section: Action Of Mechanism Of Insurmountable Btsartansmentioning
confidence: 99%
“…The side chain of residue Arg 2 forms H-bonds with the side chains of residues D263 6.58 and D281 7.32 , which is in agreement with previous reports (5, 69 -71 (Fig 12). It was previously suggested that residue K199 5.42 could form H-bonds with the C-terminal moiety of AngII, and this was also supported by docking experiments (68,(71)(72)(73). In a study in which residue R167 4.64 was shown to be important for the binding of AngII, the authors suggested that the side chain of R167 interacts with the hydroxyl group of Tyr 4 (70).…”
Section: S252mentioning
confidence: 80%
“…The amino group of the side chain of this residue may reach the carboxyl group of candesartan by forming a salt bridge (Fig. 5C), or it may interact with the biphenyl scaffold in losartan and EXP3174 via water-mediated interactions, which may explain the stronger insurmountable antagonism of candesartan compared to EXP3174, as well as the increased dissociation rate of candesartan from the receptor and decreased binding affinity of losartan, EXP3174 and candesartan upon mutation of Lys199 [47, 48]. …”
Section: Mechanism Of Insurmountable At1r Antagonismmentioning
confidence: 99%